2022
DOI: 10.26740/eds.v6n2.p128-137
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Buku Teks Bahasa Indonesia Dengan Model Sq3r Untuk Keterampilan Membaca Siswa Kelas Iv Sd

Abstract: Tujuan penilitian ini adalah untuk mengembangkan buku teks bahasa Indonesia  dengan  model SQ3R untuk keterampilan membaca siswa kelas IV SD. Adapun tujuan khusus penelitiana ini adalah (1) Mendeskripsikan proses pengembangan  model SQ3R pada buku teks  bahasa indonesia untuk keterampilan membaca siswa kelas IV SD, (2) Mendeskripsiskan kualitas buku teks yang dikembangkan. Kualitas buku teks yang dikembangkan ditinjau berdasarkan produk dan penggunaanya dikelas. Penelitian Pengembangan ini mengacu pada model  … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…Based on the results of evaluating the validity and feasibility of the module from experts, teachers, peer review, and the response of teachers and students to the module, it can be concluded that the class V science learning module using the SQ3R method is stated to be very suitable for use as learning media or learning materials as well as other learning resources for students other than textbooks or student thematic books. In line with the results of development research by Irinda Septiana, et al that the development of Indonesian language textbooks compiled using the SQ3R model for the reading comprehension skills of fifth grade students obtained a very feasible category from the validator (Septiana et al, 2022).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Based on the results of evaluating the validity and feasibility of the module from experts, teachers, peer review, and the response of teachers and students to the module, it can be concluded that the class V science learning module using the SQ3R method is stated to be very suitable for use as learning media or learning materials as well as other learning resources for students other than textbooks or student thematic books. In line with the results of development research by Irinda Septiana, et al that the development of Indonesian language textbooks compiled using the SQ3R model for the reading comprehension skills of fifth grade students obtained a very feasible category from the validator (Septiana et al, 2022).…”
Section: Resultssupporting
confidence: 78%
“…Even though there are many learning modules currently scattered in elementary schools, not many modules are designed with methods that foster reading comprehension skills in their learning. In line with the research of Irinda Septiana, et al showed the results that the development of Indonesian language textbooks for reading comprehension skills obtained a very feasible category from the validator, and after being tested, the learning outcomes of class IV students experienced an increase in terms of results pretest and posttest (Septiana et al, 2022). Research by Massonnie, et al in developing students reading comprehension of texts narrative, descriptive and hortatory exposition by using cooperative learning-based modules it was found that the findings of this study were considered valid and practical and could be used to develop students quality in reading comprehension (Massonnié et al, 2018).…”
Section: Introductionsupporting
confidence: 60%